Prevalence of dental anomalies in children analyzed by orthopantomography - Cunha, Monise Garcia Moreira; Di Nicollo, Rebeca; Teramoto, Lucia; Fava, Marcelo (Brazilian Dental Science, 2013)
Objective: To determine the prevalence of dentalanomalies in patients aged from 4-12 years-oldthrough radiographic examination. Materialand Methods: 523 panoramic radiographs andfile records were selected and analyzed by 3calibrated examiners. The material was selectedfrom the Orthodontic and Pediatric Dentistry filesof Child Clinics of the Science and TechnologyInstitute of Sao Jose dos Campos of the Sao PauloState University, including only those with highquality and contrast. Data were submitted tostatistical analysis. Results: The tabulated datawere statistically analyzed by Mann Whitneytest and Fisher’s exact test. There was a higherincidence of abnormalities in females (56.72%).It was found 7 cases (1.34%) of supernumeraryteeth, 47 cases (8.99%) of anodontia, 45 cases(8.60%) of impacted teeth, 28 cases (5.35%) ofdilacerated teeth, and 7 cases (1.34%) of ankyloseddeciduous teeth. Conclusion: According to thesample studied, dental anomalies were presentin 25.62% of the children. Considering thenumber of supernumerary, ankylosed, impactedand dilacerated teeth, there were no statisticaldifferences between genders. There was statisticaldifference between genders regarding to thenumber of anodontia, with higher predominancein females.KeywordsDental anomalies; Children; Deciduous teeth; Panoramic radiograph.